2015
DOI: 10.7314/apjcp.2015.16.17.7923
|View full text |Cite
|
Sign up to set email alerts
|

Fitting Cure Rate Model to Breast Cancer Data of Cancer Research Center

Abstract: Background:The Cox PH model is one of the most significant statistical models in studying survival of patients. But, in the case of patients with long-term survival, it may not be the most appropriate. In such cases, a cure rate model seems more suitable. The purpose of this study was to determine clinical factors associated with cure rate of patients with breast cancer. Materials and Methods: In order to find factors affecting cure rate (response), a non-mixed cure rate model with negative binomial distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
(27 reference statements)
3
4
0
Order By: Relevance
“…However, despite the increased mortality rate in N2+ women than N1 women, no significant difference was observed between N1 and N2+cure rate in this study which may be related to the difference in the effect of other items of TNM system such as the size of tumor and distant metastasis in N1 group. In line with the results of the present study, Baghestani et al indicated that patients with the involvement of more than 10 lymph nodes had 12 months less survival and 24% more mortality. In another study, Baghestani et al showed a significant relationship between survival and lymph node involvement.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, despite the increased mortality rate in N2+ women than N1 women, no significant difference was observed between N1 and N2+cure rate in this study which may be related to the difference in the effect of other items of TNM system such as the size of tumor and distant metastasis in N1 group. In line with the results of the present study, Baghestani et al indicated that patients with the involvement of more than 10 lymph nodes had 12 months less survival and 24% more mortality. In another study, Baghestani et al showed a significant relationship between survival and lymph node involvement.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study indicated that the rate of cure reduced to four times with an increase in tumor grade, mortality rate increased, and their survival reduced. Similar to the results of this study, Baghestani et al indicated that there is a significant relationship between the disease grade and survival of the patient …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations